Literature Review of Animated Films to Enhance Narrative Text Comprehension in Indonesian Elementary Students - Ningrum, Retno Dwi; Authar, Nailul; Basuki, Edi Pujo; Afandi, Mujad Didien; Aquariza, Novi Rahmania (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Narrative text comprehension is a fundamental skill for Indonesian elementary students learning English as a foreign language. However, many students still face challenges in understanding vocabulary, language features, and story structure. One effective medium to address these difficulties is the use of animated films, which combine visual and auditory elements to create a more engaging and meaningful learning experience. This study aims to review previous literature on the use of animated films to improve narrative text comprehension among Indonesian elementary students, identify effective teaching practices, and highlight existing research gaps. The method employed in this study is a systematic literature review of peer-reviewed journal articles, theses, and academic reports published over the last ten years. The review focuses on studies that examine the integration of animated films in English language learning, particularly in developing narrative comprehension skills. The findings indicate that animated films, when supported by structured learning activities such as pre-viewing preparation, guided discussions during viewing, and post-viewing reflections, can significantly enhance students’ understanding of story elements, improve vocabulary acquisition, and increase classroom participation. Furthermore, animated films support multimodal learning by enabling students to process information through both visual and verbal channels simultaneously, which helps them better grasp the meaning of the text. Despite these benefits, research specifically conducted in Indonesian elementary school settings remains limited. In addition, practical guidelines for teachers on how to effectively integrate animated films into classroom instruction are still insufficient.